Long-term prognosis of acute kidney injury: a 10 year population-based study. (25th February 2016) - Sawhney, Simon; Fluck, Nick; Levin, Adeera; Macleod, Alison; Marks, Angharad; Prescott, Gordon; Black, Corri
Abstract: Background: Acute kidney injury is serious and common, but the long-term prognosis after isolated episodes of the disorder is not well described. Therefore, giving individual patients an accurate prognosis, and planning future care, is difficult. We describe the prognosis of patients after admission to hospital with acute kidney injury. Methods: This cohort study was done in one health authority of Scotland (population 438 332). We identified individuals admitted to hospital in 2003 with and without acute kidney injury according to international criteria (Kidney Disease Improving Global Outcomes). We determined short-term (30 days), medium-term (≤1 year), and long-term (>1 year) mortality and chronic renal replacement therapy (RRT). Within split-time intervals, we also characterised the impact over time of baseline renal function, severity and recurrence of acute kidney injury, and renal recovery on mortality and chronic RRT. Findings: Of 17 630 patients, 3426 had acute kidney injury including 688 (20%) with recurrent episodes. Acute kidney injury increased short-term mortality more in patients with normal baseline function than in those with severe baseline renal impairment (adjusted hazard ratio 8·4, 95% CI 6·7–10·6 vs 2·0, 1·4–3·0). The association of acute kidney injury with mortality attenuated over time, and beyond 1 year an episode did not affect mortality in those with severe baseline renal impairment (1·1, 0·9–1·5). During 10 years of follow-up, 161 patients received chronic RRT, which was associated with acute kidney injury, but only six of these patients also had normal baseline function. There was differential effect of acute kidney injury depending on the timeframe examined: severe and unrecovered disease led to poor short-term outcomes, whereas recurrent disease and baseline renal impairment affected later outcomes. Interpretation: We show that the impact of acute kidney injury on mortality attenuates over time, and that chronic RRT is rare without baseline impairment. Short-term and long-term outcomes are differentially dependent on baseline function, recovery of acute kidney injury, and recurrence. Further study should determine the role for these factors in targeted surveillance. Funding: SS is supported by a Clinical Research Training Fellowship from the Wellcome Trust (ref 102729/Z/13/Z).